Biochar addition to compost heat recovery systems improves heat conversion yields - Pivato, Alberto; Malesani, Rachele; Bocchi, Stefano; Rafieenia, Razieh; Schievano, Andrea (Frontiers in Energy Research, 2024)
Compost Heat Recovery Systems (CHRS) represent an emerging technology to recover residual woody biomass from agroforestry and forestry activities and use the heat that is naturally produced during the aerobic biodegradation (composting). However, low oxygen concentration in the gas phase, self-drying and compaction of the compost body are often limiting efficient oxidation by microbial communities. Woodchips-derived biochar has been often proposed as a bulking agent, improver of water-retention and of oxygen accessibility in composting process, but rarely literature reported its effects in CHRS. Here, biochar (10 mm average particle size) was added at 10% (on weight basis) to chipped pruning-residues into two bench-scale controlled reactors (0.2 m 3 ), operated in parallel along 57 days. The addition of 10% (w/w) biochar in the composting body increased by around 50% biodegradation yields and improved oxidation rates over readily-biodegradable organic fractions (addition of cheese whey). Temperatures were as average 1.34 °C higher and heat extraction flux was also improved in presence of biochar (0.3 kW/m 3 ), versus 0.1 kW/m 3 in absence. Organic matter mass balance resulted in around 50% higher biodegradation yield and improved oxidation rates over readily-biodegradable organic fractions. Microbial analysis highlighted a higher concentration of thermophilic species and a lower concentration of well-known pathogenic and antibiotic-resistant genera in presence of biochar.